Aggregation-Induced Emissive Scintillators: A New Frontier for Radiation Detection and Imaging - Li, Xinyi; Yu, Jiafu; Fan, Yinghao; Gao, Yuting; Niu, Guangda (Nano-Micro Letters, 2025)
Aggregation-induced emission (AIE) is a unique phenomenon where certain organic materials exhibit enhanced luminescence in their aggregated states, overcoming the typical quenching observed in conventional organic materials. Since its discovery in 2001, AIE has driven significant advances in fields like OLEDs and biological imaging, earning recognition in fundamental research. However, its application in high-energy radiation detection remains underexplored. Organic scintillators, though widely used, face challenges such as low light yield and poor radiation attenuation. AIE materials offer promising solutions by improving light yield, response speed, and radiation attenuation. This review summarizes the design strategies behind AIE scintillators and their very recent applications in X-ray, γ-ray, and fast neutron detection. We highlight their advantages in enhancing detection sensitivity, reducing background noise, and achieving high-resolution imaging. By addressing the current challenges, we believe AIE materials will play a pivotal role in advancing future radiation detection and imaging technologies. Highlights: 1 Summarizes the high quantum efficiency and rapid response of aggregation-induced emission (AIE) materials in radiation detection, showcasing their advantages in high-energy radiation signal detection. 2 Reviews the progress in AIE materials’ radiation response for efficient detection of X-rays, γ rays, neutrons, and other radiation types. 3 Long term stability, device integration, and adaptability to diverse radiation forms remain key challenges for broader AIE material applications.